Analysis of Main Character Amy Dorrit in the Film "Little Dorrit" by Charles Dickens - Agung Prasetyo; Wildah Saputri (Candradimuka: Journal of Education, 2023)
Purpose This study the author wants to analyze the main character Amy Dorrit in the film Little Dorrit by Charles Dickens (1812-1870). The author hopes that students of Indraprasta PGRI University and other readers will know more about Dickens' work and ideas. The research used descriptive qualitative method. The research was conducted in two ways; the first source of data, the author used Little Dorrit. The second source of data the author uses opinions and criticisms about the film Little Dorrit, information about the character of the girl in the Victorian era and the biography of Charles Dickens, in addition to that the author also uses a literary approach to analyze the film. The main character in the film Little Dorrit is Amy Dorrit. Amy, otherwise known as Little Dorrit, lives in the Marshalsea Prison with her father, William, who is the prison's longest serving inmate. Although born and bred in the prison, Amy is far from being downtrodden and has grown up to be a gentle and kind-hearted yet enterprising and spirited young woman. Amy became a major figure in this story because of the intensity of his presence from the beginning to the end of the story and has a relationship with each character in the story. Character that is in the main character is kind, merciful, modest, and polite. The writer analyses the subordinate leaders such as attitudes, and actions to clarify the nature and affect the main character.